Special issue: Social media and well-being - Valkenburg, Patti M.; Beyens, Ine; Meier, Adrian; Vanden Abeele, Mariek (Current Opinion in Psychology, 2022)
The effect of social media use on well-being is among the hottest debates around the world. This special issue brings together scholars from the social and behavioral sciences to reflect on the breadth of research published in recent years. The collaborative contributions of these scholars resulted in 26 articles on the effects of social media use on well-being. Beyond synthesizing the state of the literature, the invited articles address key risk and resilience factors, such as self-esteem, cyberbullying, body image, and (romantic) relationships. Additionally, they discuss important mechanisms to explain the effects of social media use on well-being, such as social comparison, self-regulation, and social displacement. Finally, they dedicate special attention to the uses and effects of social media among specific groups (older people, parents), contexts (the workplace) and regions (the Global South